2019
DOI: 10.1093/ecco-jcc/jjz156
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis and High-dimensional Phenotypic Mapping of Mononuclear Phagocytes in Mesenteric Lymph Nodes Reveal Differences Between Ulcerative Colitis and Crohn’s Disease

Abstract: Background and Aims Crohn’s disease [CD] and ulcerative colitis [UC] are distinct forms of inflammatory bowel disease. Heterogeneity of HLA-DR+SIRPα + mononuclear phagocytes [MNPs], including macrophages [MΦ], monocyte-derived [Mono] cells, and dendritic cells [DCs], was reported in gut tissue but not yet investigated in mesenteric lymph nodes [MLNs] of IBD patients. We here compared the phenotype, function, and molecular profile of HLA-DR+SIRPα + MNPs in CD and UC MLNs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…These data corroborated with those from mice, where it has been shown that mLN Mfs poorly activate naïve T cells and were involved in clearing apoptotic cells and promoting B cell activation (314,315). To note, using CyTOF, Chapuy et al described 7 mLN Mf subsets in IBD patients (313), but their location, function and disease involvement remain to be deciphered.…”
Section: Macrophages In Mesenteric Lymph Nodessupporting
confidence: 70%
See 4 more Smart Citations
“…These data corroborated with those from mice, where it has been shown that mLN Mfs poorly activate naïve T cells and were involved in clearing apoptotic cells and promoting B cell activation (314,315). To note, using CyTOF, Chapuy et al described 7 mLN Mf subsets in IBD patients (313), but their location, function and disease involvement remain to be deciphered.…”
Section: Macrophages In Mesenteric Lymph Nodessupporting
confidence: 70%
“…However, these mLN Mfs poorly activated naïve T cells and did not contribute to Th17 plasticity toward Th1 and Th1/Th17 profiles compared to mLN SIRPα + DCs (313). Finally, mLN Mfs highly expressed genes involved in phagocytosis and in leucocyte chemotaxis (313). These data corroborated with those from mice, where it has been shown that mLN Mfs poorly activate naïve T cells and were involved in clearing apoptotic cells and promoting B cell activation (314,315).…”
Section: Macrophages In Mesenteric Lymph Nodessupporting
confidence: 65%
See 3 more Smart Citations